Redesigning the Provision of Aggravation in Property Crime during the Pandemic - Oktobrian, Dwiki; Basworo, Handityo; Amalia, Syarafina; Basuki, Fernando; Lumempow, Euodia; Jain, Vaibhav (Jurnal Suara Hukum, 2024)
One of the things that has been potentially overlooked in the development of criminal law during the Covid-19 pandemic is how the Prosecutor's Office and the Courts view the seriousness of property crimes. Every state has set up a social safety net to ensure that individuals are able to live without hunger despite the economic slowdown, and this initiative also comes along with a more intense social concern from the social environment. This article seeks to uncover the patterns of prosecution and imprisonment by judges for property crimes during the pandemic, which are inappropriate as everyone experiences family loss and economic hardship. The primary data in this article uses interviews with prosecutors and judges, then validates it in data on the length of prison charges and prison sentences recorded in the Case Tracking Information System (SIPP) in the Semarang District Court, Banyumas District Court, and Purwokerto District Court. The results of this research reveal two important things. First, prosecutors and judges in Indonesia during the Covid-19 pandemic did not aggravate prison charges and prison sanctions, even the Penitentiary tended to accelerate the assimilation process or shorten the duration of imprisonment. Second, property crimes committed during the pandemic are relevant to aggravate the threats and penalties, because they make life difficult for people who are financially and psychologically weak. Indonesia should consider revising the sentencing guidelines in the National Criminal Code before it becomes effective in 2026.